Structural evolution of biomass char and its effect on the gasification rate. (1st January 2017) - Fatehi, Hesameddin; Bai, Xue-Song
Highlights: A comprehensive model was developed to describe the evolution of biomass char structure. An effectiveness factor was used to account for the intra-particle chemical and physical processes. The effect of the structural evolution of the multi-pore structure on biomass char reactivity was analyzed. The multi-pore model yields results in satisfactory agreement with experiments. Abstract: The evolution of char porous structure can affect the conversion rate of the char by affecting the intra-particle transport, especially in the zone II conversion regime. A multi-pore model based on the capillary pore theory is developed to take into account different conversion rates for pores with different radii. The model is valid for biomass chars produced under relatively low heating rates, when the original beehive structure of the biomass is not destroyed during the pyrolysis stage. The contribution of different pores with different radius is taken into account using an effectiveness factor presented for each pore radius with respect to different reactions. As the char conversion proceeds, the pore enlargement increases the contribution of micro-pores; consequently the effective surface area will increase. The increase in the effective surface area leads to an increased reactivity of char during the entire conversion process. This model is used to analyze the steam gasification process of biomass char of centimeter sizes. The results from the present multi-pore model are in better agreement with experimental data than those from a corresponding single pore model. Since the multi-pore model accommodates the detailed intra-particle transport, it is a useful basis toward developing a more predictive model for biomass char gasification.